Case Report: Zinc deficiency as a modifiable risk factor for enfortumab vedotin–induced cutaneous adverse events - Nishizawa, Aya; Itoh, Masaya; Inoue, Midori; Makiguchi, Moe; Koga, Fumitaka (Frontiers in Oncology, 2025)
BackgroundEnfortumab vedotin (EV) is effective for advanced urothelial carcinoma, but cutaneous adverse events (CAEs) remain a major barrier to treatment continuity. Intertriginous eruptions resembling symmetrical drug-related intertriginous and flexural exanthema (SDRIFE) are particularly problematic. Zinc deficiency causes similar dermatoses, suggesting a possible link with EV-induced skin toxicity.Case presentationWe retrospectively analyzed 10 EV-treated patients with advanced urothelial carcinoma. Serum zinc levels were measured at the onset of CAEs or dysgeusia, and all patients had subnormal zinc levels (80–130 μg/dL). SDRIFE-like rash occurred in six patients, dry skin in five, and maculopapular rash in four. Patients with SDRIFE-like rash had significantly lower zinc levels than those without (median: 63 μg/dL vs. 70 μg/dL, P = 0.041). Zinc supplementation (100–150 mg/day, 2–4 weeks) was administered in four patients with grade ≥2 skin rash and dysgeusia. Three with SDRIFE-like rash improved within days and resolved within 14 days despite poor response to corticosteroids, whereas dry skin improved only partially and dysgeusia did not improve.DiscussionThese findings suggest that zinc deficiency may predispose EV-treated patients to SDRIFE-like eruptions by amplifying skin vulnerability typical of zinc-deficient states. Zinc supplementation showed rapid benefit in corticosteroid-refractory cases, pointing to its potential as a supportive adjunct.ConclusionZinc deficiency may represent a modifiable factor in EV-induced skin toxicity, particularly SDRIFE-like rash. Monitoring zinc status and considering supplementation could help mitigate rash severity and support treatment adherence and continuity, which is critical for patients with advanced urothelial carcinoma receiving EV as one of the last available treatment options.